Tavoite 5b -ohjelman suuntautuminen - Oksa, Anna-Liisa (Maatalouden taloudellinen tutkimuslaitos, 1997)
The area of application, lines of action, and measures of Objective 5b of the EU are examined in the following. The regional division used as the basis for regional development in Finland will be described first, followed by an outline of the EU programmes applied in Finland. The implementation of the programme based on Objective 5b has been examined in the two areas used in the study concerning changes in farmers incomes and the effects of these on the accrued taxes. The Upper Savo region in the Eastern Finland as well as the other research area located in the Southwestern Finland are almost fully covered by Objective 5b concerning the rural industries, except for certain municipalities in the southern parts of the areas in question, which are included in Objective 2 concerning the regions with structural changes in the manufacturing industries. The paper presents the special features of the areas concerned as well as the focal areas of the programme based on Objective 5b in the provinces corresponding to these areas. The study covers 164 individual projects, and the orientation of these can be examined at the level of the provincial areas, which is more extensive than the research areas, on the basis of the names and cost estimates of the projects.
Keywords: Ma; maaseudun aluekehittäminen; aluesuunnittelu; maaseutu; regional development; regional planning; rural areas